RefSeq curation and annotation of stop codon recoding in vertebrates. Issue 2 (7th December 2018) - Rajput, Bhanu; Pruitt, Kim D; Murphy, Terence D
Abstract: Recoding of stop codons as amino acid-specifying codons is a co-translational event that enables C-terminal extension of a protein. Synthesis of selenoproteins requires recoding of internal UGA stop codons to the 21st non-standard amino acid selenocysteine (Sec) and plays a vital role in human health and disease. Separately, canonical stop codons can be recoded to specify standard amino acids in a process known as stop codon readthrough (SCR), producing extended protein isoforms with potential novel functions. Conventional computational tools cannot distinguish between the dual functionality of stop codons as stop signals and sense codons, resulting in misannotation of selenoprotein gene products and failure to predict SCR. Manual curation is therefore required to correctly represent recoded gene products and their functions. Our goal was to provide accurately curated and annotated datasets of selenoprotein and SCR transcript and protein records to serve as annotation standards and to promote basic and biomedical research. Gene annotations were curated in nine vertebrate model organisms and integrated into NCBI's Reference Sequence (RefSeq) dataset, resulting in 247 selenoprotein genes encoding 322 selenoproteins, and 93 genes exhibiting SCR encoding 94 SCR isoforms.